Broadband observations of the naked-eye [gamma]-ray burst GRB 080319B - Racusin, J.; Karpov, S.; Sokolowski, Marcin; Granot, J.; Wu, X.; Pal’shin, V.; Covino, S.; van der Horst, A.; Oates, S.; Schady, P.; Smith, R.; Cummings, J.; et al. (Nature Publishing Group, 2008)
Long-duration c-ray bursts (GRBs) release copious amounts of energy across the entire electromagnetic spectrum, and soprovide a window into the process of black hole formation from the collapse of massive stars. Previous early opticalobservations of even the most exceptional GRBs (990123 and 030329) lacked both the temporal resolution to probe theoptical flash in detail and the accuracy needed to trace the transition from the prompt emission within the outflowto externalshocks caused by interaction with the progenitor environment. Here we report observations of the extraordinarily brightprompt optical and c-ray emission of GRB 080319B that provide diagnostics within seconds of its formation, followed bybroadband observations of the afterglow decay that continued for weeks. We show that the prompt emission stems from asingle physical region, implying an extremely relativistic outflow that propagates within the narrow inner core of atwo-component jet.